Security-aware elasticity for NoSQL databases in multi-cloud environments. (2017) - Naskos, Athanasios; Gounaris, Anastasios; Mouratidis, Haralambos; Katsaros, Panagiotis
We focus on horizontally scaling NoSQL databases in a cloud environment, in order to meet performance requirements while respecting security constraints. The performance requirements refer to strict latency limits on the query response time. The security requirements are derived from the need to address two specific kinds of threats that exist in cloud databases, namely data leakage, mainly due to malicious activities of actors hosted on the same physical machine, and data loss after one or more node failures. A key feature of our approach is that we account for multiple cloud providers offering resources of different characteristics. We explain that usually there is a trade-off between performance and security requirements and we derive a model checking approach to drive runtime decisions that strike a user-defined balance between them taking into account the infrastructure heterogeneity. Finally, we evaluate our proposal using real traces to prove the effectiveness in configuring the trade-offs.